Sertifikat Tanah di Garis Ombak Menimbang Hak Masyarakat Botutonuo - Karim, Aldin; Junus, Nirwan; Bakung, Dolot Alhasni (Pusat Riset dan Inovasi Nasional, 2025)
This research aims to examine the binding force of coastal border land regulations and the mechanism for issuing land certificates by the National Land Agency (BPN) in Botutonuo Village, Bone Bolango Regency. The background of this research is based on the increasing land ownership conflicts in coastal areas, particularly regarding the coastal boundary limits, which are regulated to be at least 100 meters from the highest tide line as stated in Presidential Regulation Number 51 of 2016. The research method used is empirical law with a qualitative approach, thru interviews with the community, village officials, and the National Land Agency (BPN), direct observation in the field, and literature studies. The research results show that the coastal community of Botutonuo has inherited land ownership, but when the certification process was carried out thru the PTSL, PRONA, or sporadic registration programs, problems arose because some of the land parcels for which certificates were issued were located in coastal buffer zones. This creates conflict between customary rights, the economic interests of the community, and the country's legal rules. On the one hand, land certificates provide legal certainty, access to capital, and improved well-being; however, on the other hand, their issuance has the potential to violate ecological aspects and cause disputes between residents. The findings of this research confirm the importance of harmonization between land regulations, environmental conservation, and the economic needs of coastal communities to achieve social justice and sustainable coastal space management.